DNA damage responses in ageing. Issue 11 (20th November 2019) - da Silva, Paulo F. L.; Schumacher, Björn
Abstract : Abstract : Ageing appears to be a nearly universal feature of life, ranging from unicellular microorganisms to humans. Longevity depends on the maintenance of cellular functionality, and an organism's ability to respond to stress has been linked to functional maintenance and longevity. Stress response pathways might indeed become therapeutic targets of therapies aimed at extending the healthy lifespan. Various progeroid syndromes have been linked to genome instability, indicating an important causal role of DNA damage accumulation in the ageing process and the development of age-related pathologies. Recently, non-cell-autonomous mechanisms including the systemic consequences of cellular senescence have been implicated in regulating organismal ageing. We discuss here the role of cellular and systemic mechanisms of ageing and their role in ageing-associated diseases.